Perilaku Manajemen Keuangan: Bukti Empiris pada Perusahaan - Dwi Tunggal Larasati; Dhani Ichsanuddin Nur (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of knowledge on financial management behavior towards leather companies in Magetan, in influencing financial behavior in the financial management of leather companies in Magetan Regency, and in influencing self-management behavior in leather companies in Magetan Regency. This research method is quantitative. The total population is 195 people. How to collect data using observation and questionnaires. The analysis technique uses Partial Least Squere (PLS). The results showed that, based on calculations using bootstrapping, namely, a) the final test of the estimated coefficient of Financial Knowledge (X1) on Financial Management Behavior (Y) is 0.299 in the t-count value of 5.292 and the standard reduction is 0.056. Then the p value is 0.000 <0.05; b) the final test of the estimated coefficient of Financial Attitude (X2) on Financial Management Behavior (Y) is 0.371, both the t-count value is 4.672 and the standard decrease is 0.079. So the p value is 0.000 <0.05; c) the test results of the estimated coefficient of Personality (X3) on Financial Management Behavior (Y) are as much as 0.310, the t count is 4.978 and the standard decrease is 0.063. So the p value is 0.000 <0.05. In conclusion, knowledge contributes to Magetan skin entrepreneurs to realize the right attitude of financial management. Not only knowledge but personality and financial behavior contribute to financial management attitudes, in this case it is very important because a business actor has financial knowledge, has financial attitudes and a strong personality is able to maintain his business. Everything will be realized if you show the right financial management attitude. Financial management attitudes such as managing the budget, and budget planning in managing finances are needed to be successful in maintaining and developing a business. Keywords: Personality, Financial Knowledge, Financial Behavior, Management Attitude